2020
DOI: 10.1073/pnas.2011828117
|View full text |Cite
|
Sign up to set email alerts
|

Low doses of the neonicotinoid insecticide imidacloprid induce ROS triggering neurological and metabolic impairments in Drosophila

Abstract: Declining insect population sizes are provoking grave concern around the world as insects play essential roles in food production and ecosystems. Environmental contamination by intense insecticide usage is consistently proposed as a significant contributor, among other threats. Many studies have demonstrated impacts of low doses of insecticides on insect behavior, but have not elucidated links to insecticidal activity at the molecular and cellular levels. Here, the histological, physiological, and behavioral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
117
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(123 citation statements)
references
References 75 publications
5
117
1
Order By: Relevance
“…Indeed, nAChR synaptic signalling is involved in the rhythmic firing of action potentials in clock neurons of Drosophila and other insects 36 , 42 , 63 . Furthermore field relevant concentrations of imidacloprid have also shown to cause degeneration of retinae and reduced visual acuity, providing a further possible route for neonicotinoids to disrupt light input into the clock, and hence the structural and behavioural changes observed here 47 .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Indeed, nAChR synaptic signalling is involved in the rhythmic firing of action potentials in clock neurons of Drosophila and other insects 36 , 42 , 63 . Furthermore field relevant concentrations of imidacloprid have also shown to cause degeneration of retinae and reduced visual acuity, providing a further possible route for neonicotinoids to disrupt light input into the clock, and hence the structural and behavioural changes observed here 47 .…”
Section: Discussionmentioning
confidence: 69%
“…carbachol) evoked Ca 2+ responses in larval neurons. A 2 h exposure of 2.5 µg/L imidacloprid increased gut and brain levels of superoxide reactive oxygen species and decreased mitochondrial function and ATP levels 47 . Chronic exposure of 4 µg/L imidacloprid led to degeneration of the fly retinae and loss of visual acuity, providing further evidence that field relevant sublethal concentrations of neonicotinoids bring about irreversible effects at the neuronal level.…”
Section: Introductionmentioning
confidence: 91%
“…But non-pest insects are likely to be exposed to lower doses and the downstream physiological processes that are triggered are poorly understood. In a recent study, low doses of the neonicotinoid imidacloprid were shown to stimulate a constitutive flux of calcium into neurons via the targeted ligand gated ion channels (nicotinic acetylcholine receptors – nAChRs) (Martelli et al, 2020). This causes an elevated level of ROS and oxidative stress which radiates from the brain to other tissues.…”
Section: Introductionmentioning
confidence: 99%
“…This causes an elevated level of ROS and oxidative stress which radiates from the brain to other tissues. Mitochondrial damage leads to a significant drop in energy levels, neurodegeneration and blindness (Martelli et al, 2020). Evidence of compromised immune function was also presented, supporting other studies (Chmiel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation